Fatany Thailand Cooperative Management Solutions to Improve the Benefits of the Ummah - Een Erlina; Kiki Candri; Sri Rahmany (MultiTech Publisher, 2024)
This research aims to find and analyze solutions in managing the Fatany Thailand Cooperative in increasing the benefit of the community. Tor indicators expressed in variables are related to internal factors and external factors. The variables observed in internal factors are Service, Reporting, Supervision and. Meanwhile, the variables observed in external factors are Government Regulations and Global Competition. This research uses Analytic Process (ANP) to process primary data collected from respondents representing experts, practitioners and academics. The distribution of questionnaires to respondents was carried out using non- random sampling , by selecting 7 respondents who had an in-depth understanding of developments in Thai cooperatives . The questionnaire data obtained was processed using Super Decisions software version 3.2. The research results show that the priority of the root causes of the development of Thai cooperatives in improving the benefit of the people, consists of internal problems, namely Service 35.40%, Reporting 4.43%, Supervision 5.88% and HR 35.55%. Meanwhile, external problems consist of Government Regulations 15.99 % and Global Competition 66.52%. This research also produces solutions achieved from each variable including Government Regulations, namely reducing taxes by 15.68%, Productivity Forcasting Projections by 10.71%, while the Global Competition variable has a solution following International Standards 65.75% and involving global issues of tax regulations 15.46%. i mp l ication from​​ study​​​​​​​​​ This there 's a I way to go​​​​ in conclusion as a contribution​​​​​​​ new​​ to​​​​​​ knowledge field​ economy​ And​​ finance​​​​​​​ I slam It is clear that solutions and strategies for internal factors in developing cooperatives in Thailand are a priority in providing policies to prioritize each component that is a priority in developing cooperatives in Thailand.